IMPROVEMENT OF TECHNICAL CHARACTERISTICS ON SAND-CLAY FORMS AT CONSOLIDATION BY THE AIR STREAM - A. Z. Issagulov; V. Yu. Kulikov; D. A. Issagulova; T. V. Kovalyova (Литьë и металлургия)
One way to compact large-sized sandy-clay mixtures is air-pulse molding. Spreaders used in practice in pulsed molding do not ensure homogeneity of the density at the surface and in the volume of the mold. The design of a gas flow divider is proposed that allows changing the area of the apertures due to the shaped plate and, accordingly, increasing or decreasing the speed and volume of the transmitted air fl w acting on the mixture. This ultimately guarantees uniformity of density throughout the volume of the mold.Also results of researches of voltages and the density appearing in a coma of a mix on height at sealing of sandy-clay forms by an air stream are resulted. The use of air molding with a dissector and a plate for making large-sized molds made it possible to obtain a batch of castings with high geometric accuracy and surface roughness.